2021
DOI: 10.33546/bnj.1409
|View full text |Cite
|
Sign up to set email alerts
|

“Accessibility”: A new narrative of healthcare services for people living with HIV in the capital city of Indonesia

Abstract: Background: The progress of the fight against HIV is highlighted by significant change. HIV of the past is different from HIV of the present. Healthcare services have played an essential role in achieving the optimal goals needed to end the HIV epidemic. However, people living with HIV and those at risk of catching it (PLWH) often misunderstand the rapid growth of HIV healthcare service options.Objective: This study aimed to explore the experiences of PLWH in the healthcare services featured in this study.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The only treatment for HIV infection is antiretroviral therapy (ART) (Indonesian Ministry of Health, 2019 ). ART is recommended for patients with HIV infection by disturbing the virus replication and reducing the virus levels, thereby improving immunity and reducing the occurrence of opportunistic infections and the mortality rate (Godfrey et al, 2017 ; Karyadi, 2017 ; Mahathir et al, 2021 ). Consequently, adolescents’ quality of life following ART will be improved.…”
Section: Introductionmentioning
confidence: 99%
“…The only treatment for HIV infection is antiretroviral therapy (ART) (Indonesian Ministry of Health, 2019 ). ART is recommended for patients with HIV infection by disturbing the virus replication and reducing the virus levels, thereby improving immunity and reducing the occurrence of opportunistic infections and the mortality rate (Godfrey et al, 2017 ; Karyadi, 2017 ; Mahathir et al, 2021 ). Consequently, adolescents’ quality of life following ART will be improved.…”
Section: Introductionmentioning
confidence: 99%
“…Supportive resources help to make the daily life of people living with HIV/AIDS more bearable and enable them to better adapt to the conditions of the disease (28). Another study also found that using the experiences of others living with HIV/AIDS played an important role in controlling the disease and its complications (29). In Kyakuwa's study, a group of HIV-positive nurses initiated a support process by creating safe spaces for interacting and seeking psychosocial support among themselves in a relatively secretive way (30).…”
Section: Efforts To Returnmentioning
confidence: 99%
“…Most of these studies were quantitative and evaluated the correlation between ART adherence and knowledge, support system, and education level (Fahriati et al, 2021 ; Haryadi et al, 2020 ; Sianturi & Dorothea, 2020 ). Few qualitative studies have examined HIV in Indonesia, including the ART regimen (Agnes & Songwathana, 2021 ; Edison et al, 2021 ; Harison et al, 2020 ; Ismail et al, 2022 ; Mahathir et al, 2021 ; Nuraidah et al, 2022 ; Nurfalah et al, 2019 ). However, none of previous studies examined the process of ART adherence among PLWH.…”
Section: Introductionmentioning
confidence: 99%